KOLEKSI PENDING EMAS: TIPOLOGI DAN TEKNIK PERTUKANGAN LOGAM - Mohamad Zawawi, Hayati; Musa Kahn, Sabzali; Raja Ahmed, Raja Suriaty (JURNAL MELAYU SEDUNIA, 2019)
This article discusses gold waist buckle research which is a type of an exclusive ornament. The gold waist buckle is considered as a symbol of status among Southeast Asians. It is one of the highly revered cultural ornaments among the Malay community and the Baba Nyonyas. It is mainly worn by the King and the royal family while for Baba Nyonya, it is worn by the affluent and high-rank family. Thus, the research focuses on the Malay and Baba Nyonya gold waist buckle collection of the Department of Museums Malaysia. The qualitative method approach is adopted for this research. This article examines the typology and handiworks technique of the gold waist buckle collection. For data accumulation, there were three methods applied which comprised observation, interview and documentation. According to analysis findings, the typology of the gold waist buckle is divided into two shapes namely geometric and organic. Apart from that, the outer frame structure of pointed and hacked shape gives a special identity to gold waist buckle typology. In this research, there are seven metalwork techniques applied to the Department of Museums Malaysia gold waist buckle collection. It indicates an influence of foreign and local handiwork techniques which is assimilated with the workmanship and creativity of local goldsmith.